Dynamics of Health Budget Refocusing and its Implication to Covid-19 Pandemic Mitigation in Remote Archipelagic Areas (A Case Study in Sumba Tengah Health Agency, Nusa Tenggara Timur Province) - Serlie K. A. Littik; Dominirsep O. Dodo; S. P. Manongga (Health Notions, 2023)
Health crisis due to Covid-19 Pandemic should be mitigated to reduce the opportunity for a greater health loss. One key factor for the success of health intervention is the availability and proper use of budget. Districts lacking fiscal capacity should choose the best option available to address the issue. This aims to describe the dynamics of the health budget refocusing on mitigation of Covid-19 and its implication to the achievement of health development targets in remote archipelagic areas. This is a qualitative study conducted in Sumba Tengah District Health Agency, in October 2020. Data are collected through semi-structured interviews with several key informants. The policy of budget refocusing to mitigate Covid-19 at the district level is a highly dynamic and complex process. Understanding of budget refocusing policy among district personnel vary. Implementation of budget refocusing policy potentially create new long and short terms problems within the health sector. Keywords: budget refocusing; Covid-19; remote archipelagic areas